Keragaan dan Keragaman Genetik Karakter Agronomi Galur Mutan Putatif Gandum Generasi M5 - Febrianto, Eka Bobby; Wahyu, Yudiwanti; Wirnas, Desta (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
The cultivation of wheat in Indonesia especially at medium-low altitude faces problems such as high temperatures whicheffect negativelyon the yield. The aims of this research was to obtain informations on performance, genetic variability and heritability of agronomic characters of wheat putative mutant lines on M5 generation. Genotypes evaluated in the study consisted of 98 putative mutant lines of M5 generation and six varieties as checks, namely Dewata, Selayar, Oasis, Rabe, Kasifbey, and Basribey. The research was conducted at Research Station of IOCRI (Indonesian Ornamental Crops Research Institute), Cipanas. Genotypes were arranged in an augmented, randomized block design. Result of the experiment showed that high heritability estimates were observed for plant height (83.03%), tiller number (61.75%), days to flowering (85.41%), days to maturity (67.45%), spike length (70.25%), spikelet number (65.08%), unfilled grain number (71.49%), seed number per spike (75.16%), seed weight per spike (81.69%), and seed weight per plant (74.21%). The estimated genotypic coefficient of variation (GCV) were high for unfilled grain number(26.35%) and seed weight per plant (18.35%). Based on seed weight per plant, 30 best putative mutant lines were selected.Keywords: Augmented design, heritability, Triticum aestivum